Implementasi E-Commerce untuk Pengembangan Market Produk Kewirausahaan Mahasiswa - Alexius Endy Budianto; Didik Iswahyudi; Eris Dianawati (Jurnal Pemberdayaan Masyarakat, 2020)
The development of student entrepreneurship at the University of Kanjuruhan Malang is starting to show results. This is very supportive of government programs in their development in line with increasing economic growth. Furthermore, it has an impact on student entrepreneurial actors to be more creative and innovative in effective marketing strategic planning. Most entrepreneurial students have difficulty developing because they do not understand how to market a product effectively, display product packaging attractively so that it has high selling value and manages their business well. On this occasion, we aim to provide solutions through the Entrepreneurship Development Program of the University of Kanjuruhan Malang which collaborates with micro, small and medium enterprises (MSMEs) in Malang City and Regency, in the form of a digital marketing strategy, namely e-commerce. The method we use in this activity is conducting workshops by forming student groups according to their target products and market reach, and providing assistance to these student groups. The investment that we provide is in the form of e-commerce applications. The results of the investment show a significant change in marketing among entrepreneurial students at Kanjuruhan University of Malang.